Stealing magic : a Sixty-eight rooms adventure - Malone, Marianne (Random House, 2011)
Chicago sixth-graders Jack and Ruthie return to the Thorne Rooms at the Art Institute of Chicago and once again go back in time while trying to stop an art thief from endangering the miniature rooms.